Road orientation affects the impact of roads on wildlife - Mulero-Pázmány, Margarita Cristina; Rollán, Laura; D'Amico, Marcello; González-Suárez, Manuela (CSIRO Publishing, 2022)
Context: Understanding the factors determining the impacts of roads and how they fragment landscapes limiting the movement of animals, is key to implement efficient mitigation measures. Aims: Here we investigate if road orientation in relation to limiting resources, a largely overlooked factor on road impact assessments, can influence the movement of animals within a landscape where water resources are spatially clustered. Methods: We evaluated movement by monitoring animal tracks on unpaved roads: two with a North–South orientation and two with an East–West orientation. Key results: Animals were more likely to follow roads leading to limiting resources (i.e. East–West orientation), confirming human linear structures can facilitate wildlife movements. Carnivores were more likely to follow roads with any orientation and for longer compared to ungulates, whereas ungulates followed roads mainly in the orientation of limiting resources. Conclusions: Road orientation affects how roads influence the movement of animals in landscapes where resources are distributed along a spatial gradient with different effects for ungulates and carnivores. Implications: The key implications of this work affect the planning and implementation of mitigation strategies and safety measures. Our results suggest road-crossing infrastructure and fences will be most important in roads traversing a gradient to allow wildlife movement while preventing collisions. For roads along a gradient, crossing structures may be less important, but fences or appropriate signage could be useful to prevent or warn drivers of animals travelling on the road.
Keywords: Parque Natural Entorno de Doñana; Road; Doñana; Ungulates